Voluntary Carbon Disclosure on Financial Performance and Investment Efficiency: A Study in Indonesia - Musthafa, Afif; Arifin, Taufiq (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to seek empirical evidence on the effect of voluntary carbon disclosure on financial performance and investment efficiency of companies in Indonesia before the HPP Law. This study uses panel data analysis with a sample of 644 companies listed on the Indonesia Stock Exchange. The 2019-2020 sample was used because in 2021 there is already a law governing carbon tax. The results showed that the company's voluntary carbon disclosure has no influence on financial performance, both in the short and long term but has a positive influence on the company's investment efficiency. This research highlights the importance of voluntary carbon disclosure in building trust and support from stakeholders, which can provide benefits to the company in the form of investment efficiency and better financial performance. This research presents a more complex measure of voluntary carbon disclosure linked to financial performance and investment efficiency.